TEKNIK BUDIDAYA MIKROORGANISME TANAH UNTUK MENINGKATKAN KESUBURAN MEDIA TANAM - Toto Supartono; Ilham Adhya; Yayan Hendrayana (Politeknik Negeri Sriwijaya, 2023)
Fertility of planting media is one of the critical success factors in plant production activities. The use of local microorganisms in increasing the fertility of planting media can be an alternative in the use of synthetic fertilizers and help realize the independence of rural communities in plant cultivation. The purpose of this activity is to provide knowledge about soil microorganism breeding techniques to increase the fertility of the growing media. The target groups in this activity are the Women Farmers Group (KWT) and the Mandapajaya Village Community, Cilebak District, Kuningan Regency. In accordance with the expected target, the activity was attended by KWT and representatives of farmers. All participants who attended followed the activity until it was finished. The participants also asked several questions related to the material presented during the discussion session. At the end of the discussion, the participants also said that they understood the material that had been delivered and planned to implement the material. Keywords: cultivation, fertility, microorganisms, soil, plants